Answer:
part A 6 out comes.
Step-by-step explanation:
for part A (C,F) (C,P) (C,T) (F,P) (F,T) (P,T)
Answer:
Part A. C=9
Part B. (w+3)² =139
Part C. w = 8.8 inch
Step-by-step explanation:
Given from the question length of the the picture = (2w+12) inches
Width of the picture = w inches
Area of the picture = 260 inch²
Part A. Area of the picture with the given dimensions= w×(2w+12)
Or w(2w+12) = 260
2w²+12w = 260
2(w²+6w) = 2×(130)
w²+6w = 130
Or w²+6w +9 = 130+9 ⇒ which is in the form of w²+6w+c = 130+c
Therefore for c = 9 we will get a perfect square trinomial.
Part B. As we have seen the equation in part A.
As required equation will be (w+3)²=139
Part C. Since (w+3)² = 139
Then by taking under root on both the sides of the equation
(w+3) =√139 = 11.8
(w+3)-3=11.8-3
w = 8.8 inch
Answer:
x = 7/3
Step-by-step explanation:
4x - 2 = x + 3 + 2
4x - 2 = x + 5
Rearranging the terms, we get,
4x - x = 5 + 2
3x = 7
x = 7/3
Hence, x = 7/3.
Answer: You can multiply the top equation by -1 to eliminate the x variable.
And the solution is (2,4/3) in case you need it.
Step-by-step explanation:
2x + 3y = 8
2x + 6y = 12
If you multiply the upper equation or down equation by one, you will be able to eliminate the x variable.
-1( 2x + 3y) = -1(8) New equation: -2x -3y = -8.
Add the new equation you got by multiplying the top equation by -1 to the bottom equation.
Add them: -2x -3y = -8
2x + 6y = 12
3y = 4
y = 4/3
You can now input the value for y into the one of the equations and solve for x.
-2x - 3(4/3) = -8
-2x -4 = -8
+4 +4
-2x = -4
x = 2